Formation and exudation of biphenyl and dibenzofuran phytoalexins by roots of the apple rootstock M26 grown in apple replant disease soil. (December 2021) - Busnena, Belnaser A.; Beuerle, Till; Mahnkopp-Dirks, Felix; Winkelmann, Traud; Beerhues, Ludger; Liu, Benye
Abstract: Apple replant disease (ARD) is a severe soil-borne disease frequently observed in apple tree nurseries and orchards worldwide. One of the responses of apple trees to ARD is the formation of biphenyl and dibenzofuran phytoalexins in their roots. However, there is no information on whether or not these phytoalexins are exuded into the soil. To answer this open question, a model system was established using the ARD-sensitive apple rootstock M26 ( Malus  ×  domestica Borkh. Rosaceae) and GC-MS analysis in combination with an in-house GC-MS database including retention indices. We have detected a total of 35 phytoalexins, i.e. 10 biphenyls and 25 dibenzofurans in root samples, thereby adding eight compounds to the previously reported 27 phytoalexins of Malinae species. When in vitro cultured M26 plantlets were treated with yeast extract, all the 35 phytoalexins were formed in the roots and 85.2% of the total phytoalexin amount was exuded into the culture medium. In roots of M26 plants grown in ARD soil in pot, 26 phytoalexins were detected and their exudation was demonstrated using two independent approaches of collecting root exudates. In a modified dipping experiment and a soil-hydroponic hybrid setup, the exudation rate was 39.5% and 20.6%, respectively. The exudation rates for individual phytoalexins differed, indicating controlled exudation processes. The exuded phytoalexins may play an important role in shaping the soil microbiome, which appears to greatly influence the development and severity of ARD. Graphical abstract: Biphenyl and dibenzofuran phytoalexins were produced and exuded by root of apple rootstock M26 grown in apple replant disease (ARD) soil. Image 1 Highlights: Thirty-five phytoalexins were identified in roots of the apple rootstock M26. Phytoalexins were induced in yeast extract-treated roots of in vitro M26 plantlets. Phytoalexins were induced in roots of M26 plants grown in apple replant disease soil. Aliquots of phytoalexins produced in roots were actively exuded into medium or soil.